Status , Botanical Description , Natural Distribution Zone , Propagation Practices and Conservation Efforts of Hildegardia Populifolia (Roxb.) Schott & endl. - a Threatened Tree Species of Dry Tropical forests in India - Sarcar, Manoj Kumar; Sarcar, Aruna Basu (Indian Forester, 2002)
Hildegardia populifolia is one of the endemic and threatened tree species of the Peninsular India. During the recent past , 13 mature trees and 11 young natural regenerations of this species have been identified in Dry mixed deciduous forests of Parigam Reserved Forests in Kalrayan hills of Kallakurichi Forest Division , Tamil Nadu during 1998 to 2001 (up to June 11 , 2001). Status of this threatened tree species , Hildegardia populifolia (Roxb.) Schott&Endl. Is reassessed. Botanical description of the species with growth habit , phoenology , salient morphological features with distinct identification character and silvicultural characters are provided with illustrative diagrams and photographs. Natural distribution zone of the species along with the places of endemism and potential areas are described with related maps. Immediate need to protect and propagate this critically endangered species is emphasised. Methods of artificial reproduction of the species with nursery techniques , germination stages , development of seedlings are explained. Finally conservation efforts taken so far and further measures recommended to plug the further erosional process of the species from its natural habitat are discussed.